GREEK IT START-UPS – AN ANALYSIS OF FOUNDER’S PERCEPTIONS - Theocharis Stylianos SPYROPOULOS (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
The study examines the Greek IT start-up ecosystem, analyzing the founders’ views, strategy, and current perception regarding their ICT start-ups. The study examines perception of more than 120 founders of Greek IT start ups who participated in exhibitions as start-up companies during 2018 and 2019 and had completed at least one accelerator program. The literature review provides a wide range of factors that can determine the success of start-up companies with a special focus on IT (Information Technology). The research questionnaire was designed, based on findings of the previous academic studies. The present research involves primary research and the use of structured questionnaires. 130 questionnaires were distributed to the founders of the startups, and were collected immediately. In certain cases brief discussions with the responders took place, in order to clarify certain points and to confirm validity of the data. The data were encoded and the advanced statistical analysis software (SPSS) was used in order to proceed to statistical analysis. The study examines the relationships between variables which, according to the literature review, have significant impact on the success of a start-up, such as previous experience and education level of start-up founders, self evaluation regarding success of their ventures, number of founders, current challenges, competition and degree of innovation. The research findings provide a deeper understanding of the dynamics of Greek IT start-ups, in terms of competitive advantage, value to end customer, need for financial support and founder’s expectations. The findings are useful to entrepreneurs as they strive to increase the success rates of current and future projects as well as to the wider innovation ecosystem, e.g. business angels, venture capital firms, the state etc., to further improve their success rates or design and implement policies for innovation promotion. Finally, key areas for further research are highlighted.